2022
DOI: 10.3390/land11071074
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ANNs and Cellular Automata–Markov Chain to Simulate Urban Expansion with Annual Land Use Data

Abstract: Accurately simulating and predicting the urban expansion process, especially in expeditious urbanization areas, is an important aspect of managing limited land resources and adjusting flawed land use policies. This research was conducted on the basis of a high-temporal-resolution land use dataset to precisely model urban expansion in a rapidly developing zone by integrating the Artificial Neural Network (ANN), cellular automata (CA), and Markov Chain (MC). An urban suitability index (USI) map was created using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
1
11
0
3
Order By: Relevance
“…For example, a study on the upper Rwizi catchment [64], reported that cropland covered majority of the land cover and increased between 2000-2014, while grazing land reduced; all due to conversions from and to other land cover classes respectively. This is similar to findings by [65], on the Lake Mburo pastoral area, where farmland increased by conversion from wetland area during the 1987-2020 period [26], in the Mt. Elgon region (1978-2020), reported a similar conversion trend.…”
Section: Reflection On Land Cover Conversionssupporting
confidence: 88%
“…For example, a study on the upper Rwizi catchment [64], reported that cropland covered majority of the land cover and increased between 2000-2014, while grazing land reduced; all due to conversions from and to other land cover classes respectively. This is similar to findings by [65], on the Lake Mburo pastoral area, where farmland increased by conversion from wetland area during the 1987-2020 period [26], in the Mt. Elgon region (1978-2020), reported a similar conversion trend.…”
Section: Reflection On Land Cover Conversionssupporting
confidence: 88%
“…Simulating fine-scale changes in urban land use is an important way to explore the ecological risks manifested by the loss of the ecosystem services provided by an ecological space or by an increased sensitivity of the ecological environment [ 22 , 23 ]. However, simulations of urban expansion that consider “urban–non-urban” or land use changes involving transitions between multiple land types generally combine impervious surfaces into a single type of urban land [ 24 , 25 ]. Research remains sparse on the simulation of the spatiotemporal evolution of various types of construction land such as industrial land, mining land, urban construction land, and rural settlements.…”
Section: Introductionmentioning
confidence: 99%
“…However, prior researches on land use change modeling have mostly concentrated on transitioning between common land types, such as impermeable surfaces, cultivated land, etc. (Hu et al, 2022;Xu et al, 2022), while there is still little knowledge on nature reserves, which are composed mainly of wetlands, such as freshwater swamps, saline swamps, Phragmites australis fields, and Suaeda salsa area, et al (Bao et al, 2019;Athapaththu et al, 2020). Moreover, by taking into account the interactions within different patches, the CA-based model has been widely used to simulate the complicated self-organization behavior of land use (Guan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%